Caracterização cristaloquímica e cristalofísica sobre a gênese de turmalina e columbita-(fe) de pegmatitos das regiões de Solonópole e Berilândia no Estado do Ceará - Freire, Débora Macêdo do Nascimento (2020)
The Pegmatitic District of Solonópole-Banabuiú (DPSB) is located in the central-estern portion of the State of Ceará, embedded in the paragnáissico basement of the Borborema Province, Domain Ceará Central. It is the most economically significant in the region, which encompasses the Ceará Central Domain, and its main mineralizations are associated with the lithium-beryl-tantaliferous character of the bodies. In this work, two pegmatitic bodies located in the DPSB with distinct mineralogical characteristics were studied, the pegmatite Mendonça, located in the district of Berilândia and the pegmatite Auriverde located in the municipality of Solonópole, both are classified as mixed pegmatite between the homogeneous and heterogeneous types, without zoning visibly well defined complete. It is a complex pegmatite, forming replacement bodies (pockets) of muscovite, quartz and beryl, with well-developed crystals. It falls into the class of Rare Earth Elements, of the LCT family. The mineralogy of pegmatite Auriverde differs from pegmatite Mendonça in the presence of lithium minerals. The tourmaline of this mine has a variation from green to blue, while the variation that occurs in the tourmaline of the Mendonça mine is green to yellow. In the pegilite of Berilândia, crystallophysical characterization was carried out through X-ray diffraction using the powder method and micro-Raman spectroscopy in samples of tantalates / columbites, indicating that they are Fe columbites, micro-Raman spectrometry in muscovite samples suggest through the spectra obtained that it is a muscovite with a high OH content. The crystallochemical characterization was done by electron probe analyzes on plagioclase, muscovite, tourmaline and oxides. In plagioclase, SiO2 = 67.68%, Al2O3 = 10.81% and Na2O = 20.51% were obtained, which are satisfactory according to the ideal composition for albite. In muscovite the largest elements on average are Al2O3 36.07%, SiO2 = 44.56%, K2O = 10.57% and FeO = 2.27% by weight. Due to its greater amount of Al present in the sample, it is suggested that the muscovite from the Berilândia pegmatite is of primary origin. Oxides contain between 70.97% to 80.19% FeO. The largest elements constituted for green tourmaline in Al2O3 = 33.49%, MgO = 2.23% and FeO 11.45%, for yellow tourmaline Al2O3 = 33.65%, MgO = 2.24% and FeO = 11.23%, all chemically classified as schorlites. In Solonópole pegmatite, crystallophysical characterization through X-ray diffraction in monocrystal was carried out on tourmaline samples, presenting a rhombohedral crystalline structure, the spatial group is R3m and the parameters of the unit cell being a = 15.90, b = 15.90 and c = 7.12, considered favorable for a Fe-rich tourmaline crystal. Micro-Raman spectroscopy was obtained from tourmaline samples, minerals from the lepidolite group and spodumene. In these analyzes, all samples obtained a spectrum compatible with their structure according to the comparison with the RRUFF spectroscopic database. The tourmaline sample being compatible with the schorlite spectrum. Crystallochemical characterization was also carried out on lepidolite samples (Al2O3 = 28.08%, SiO2 = 48.62%, K2O = 10.17%), spodumene (Al2O3 = 20.35% eSiO2 = 67.37%), beryl (Al2O3 = 20.35% and SiO2 = 67.37%) and tourmalines (Al2O3 = 34.18%, MgO = 1.10%, FeO = 11.44%) classified as oxy-schorlites. The tourmalines of both studied pegmatites are alkaline and schorlitic. However, those of the Pegilite of Berilândia are hydroxy-species projecting in the field of granitoids and their pegmatites and associated aplites poor in Li and proximal stage, whereas the tourmaline of the Pegmatite of Solonópole are oxy-species, falling at the limit of the field of granitic pegmatites and Li-rich aplites and endogranitic / endogreisen stage. The spectra generated in tourmalines zoned by micro-Raman mapping indicate changes in redox and fO2 conditions and the presence of F in the magma / pegmatitic fluid that generates the tourmalines of the Berilândia Pegmatite.